PENGGUNAAN INDEKS PELAYANAN JALAN DALAM MENENTUKAN TINGKAT PELAYANAN JALAN PADA RUAS JALAN BANYAK LAJUR - Najid, Najid (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Level of service is important parameter for determining the road performance that is influenced by speed and volume of traffic at the certain road. In the appendix of Decree 14 year 2006 is listed categories level of service for each condition of any road function such as arterial, collector and local road. But the level of service at those decree seem too optimistic or not sensitive when applied to the current road conditions, especially on the streets of the city, that cause all the roads show at lowest level of road service or F level, especially during peak hour, so it is certainly difficult to evaluate. For those reason it is necessary to revise the provision regarding road level of service that based on a calculation of Road Service Index which consists of variables such as design speed, travel time, road capacity and traffic volume at the certain time. The revise of those provision will be proposed become the Transportation Minister Decree substitute the recent regulation. This research based on observation or field study, then IHCM method used for Level of Service analysis and mathematical method for calculating road service index. Conclusion based on comparisson of those both methods.